ETIKA KOMUNIKASI MAHASISWA TERHADAP DOSEN DALAM INTERAKSI AKADEMIK MELALUI MEDIA DIGITAL - Sudarto, Sudarto (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
This research is survey research which aims to describe the form of communication ethics between students and lecturers in carrying out the academic interactions via digital media. The data collection technique used in this research is observation technique. The research instruments used were observation sheets and daily recording sheets. The data analysis technique used is descriptive data analysis technique. The results and conclusions: The worst communication ethics between the students in digital media towards the lecturers is